Keefektifan ekstrak etanol daun petai cina(Leucaena glauca,Benth) sebagai larvasida alami terhadap kematian larva nyamuk aedes aegypti instar III - Armadhani, Riska, Dwi Astuti, SKM., M.Kes, Sri Darnoto S.KM M.PH (2014)
Lead tree (Leucaena glauca, Benth) leaves contain saponins that can be used as larvicides. The aim of this study was to determine the effectiveness of etanol ekstract of lead tree (Leucaena glauca, Benth) leaves as a natural larvicides against the mortality of the third instar larvae of Aedes aegypti. This research was an experimental research with posttest only control group design where the objects were divided into two groups: control group and treatment group. The samples were 25 larvae on each group, and it's repeated four times. So the total of samples were 700 Aedes aegypti larvae. The results showed that at concentration of 0% (control) etanol extract of lead tree leave could kill 0 larvae of Aedes aegypti, concentration of 4% could kill 7 larvae (28%), concentration of 6% could kill 18 larvae (72%), concentration of 8% could kill 21 larvae (84 %), concentration of 10% could kill 25 larvae (100%), concentration of 12% could kill 25 larvae (100%), and concentration of 14% could kill 25 larvae (100%). Based on Kruskall Wallis test analysis, it can be concluded that there was an effect of ethanol extract of lead tree (Leucaena glauca, Benth) leaves as a natural larvicides against the mortality of the third instar larvae of Aedes aegypti with a significant value of p = 0.000 (p <0.01). Ethanol extract of lead tree (Leucaena glauca, Benth) leaves at concentration of 10 % is the smallest concentration that was able to kill the third instar larvae of Aedes aegypti as much as 100 %.